IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MELALUI PENDIDIKAN SENI BUDAYA BERBASIS KEARIFAN LOKAL: STUDI KASUS DI SD NEGERI NGALIYAN 05 SEMARANG - Utomo, Yunatan Krisno; Adiyati, Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project [P5] through Javanese local wisdom-based cultural arts education at SD Negeri Ngaliyan 05 Semarang as a pedagogical strategy for strengthening character, cultural identity, and the internalization of Pancasila values in primary education. The study employed a qualitative approach with a descriptive case study design conducted at an elementary school implementing the Merdeka Curriculum in Semarang City, which is oriented toward strengthening regional and national cultural values. Data were collected through observation, in-depth interviews, and documentation studies, and were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the implementation of the Pancasila Student Profile Strengthening Project (P5) through arts and cultural education grounded in Javanese local wisdom at SD Negeri Ngaliyan 05 is effective when it is designed contextually, integratively, and reflectively. This effectiveness is reflected in thematic planning based on local culture, participatory project-based learning practices, and authentic assessment that emphasizes both the learning process and students’ character development. The study also identifies several challenges, including limited teacher pedagogical capacity, insufficient cultural arts resources, the tendency toward cultural symbolization, and gaps between national policy design and local implementation realities. As a case study, this research emphasizes that reorienting P5 from an administrative-ceremonial approach toward substantive cultural pedagogy is a crucial prerequisite for transforming character education in elementary schools. This study contributes to strengthening local wisdom-based cultural arts education as a contextual, reflective, and transformative pedagogical strategy for implementing P5 in primary education.